2009
DOI: 10.1007/s10646-009-0397-z
|View full text |Cite
|
Sign up to set email alerts
|

Environmental-endocrine control of reproductive maturation in gastropods: implications for the mechanism of tributyltin-induced imposex in prosobranchs

Abstract: Prosobranch snails have been afflicted globally by a condition whereby females develop male sex characteristics, most notably a penis. This condition, known as imposex, has been causally associated with the ubiquitous environmental contaminant tributyltin (TBT). Deduction of the mechanism by which TBT causes imposex has been hampered by the lack of understanding of the normal endocrine regulation of reproductive tract recrudescence in these organisms. We have reviewed the relevant literature on the environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(53 citation statements)
references
References 178 publications
(265 reference statements)
2
42
0
Order By: Relevance
“…The seasonal cycle in seawater temperature influences the quantity and quality of available food and regulates metabolic activities. Altogether, seawater temperature and food availability control the precise timing of breeding and spawning and is also responsible for year-to-year variations in the reproductive cycle (Sternberg et al 2010). In Bolinus brandaris, gonadal ripening and spawning were apparently triggered by the steady increase in seawater temperature during late spring to early summer, when temperature had risen by almost 10°C between March (17.3°C) and July (26.7°C).…”
Section: Vasconcelos Et Al: Reproductive Cycle Of Bolinus Brandarismentioning
confidence: 99%
“…The seasonal cycle in seawater temperature influences the quantity and quality of available food and regulates metabolic activities. Altogether, seawater temperature and food availability control the precise timing of breeding and spawning and is also responsible for year-to-year variations in the reproductive cycle (Sternberg et al 2010). In Bolinus brandaris, gonadal ripening and spawning were apparently triggered by the steady increase in seawater temperature during late spring to early summer, when temperature had risen by almost 10°C between March (17.3°C) and July (26.7°C).…”
Section: Vasconcelos Et Al: Reproductive Cycle Of Bolinus Brandarismentioning
confidence: 99%
“…During spawning, females lay eggs inside oothecas that attach to each other, forming large masses fixed to solid substrata on the sea bed (Ramón & Amor 2002). Like approximately 200 gonochoristic neogastropod species (Shi et al 2005;Sternberg et al 2010), B. brandaris is affected by imposex throughout its distributional range Solé et al 1998;Ramón & Amor 2001;Chiavarini et al 2003;Lemghich & Benajiba 2007;Vasconcelos et al 2010Vasconcelos et al , 2011Abidli et al 2009aAbidli et al , 2011Abidli et al , 2012. In B. brandaris sampled from two sites along the northern Tunisian coast (Bizerta Lagoon and small Gulf of Tunis), the stages of imposex development varied between VDS 1 and VDS 4.3, with all imposex indices being significantly higher in snails from the Bizerta lagoon (Abidli et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…M2 appears to be more potent than both the M1 metabolite and the parent compound ). VZ has also been shown to induce cytochrome P450-dependent aromatase activity (CYP19) which converts testosterone into estradiol (Sanderson et al 2002) and which has been identified in several molluscs species (Sternberg et al 2010). Therefore, due to the reprotoxic properties of VZ and its metabolites, all commercial products containing this active ingredient have been banned in Europe since 2006.…”
Section: Introductionmentioning
confidence: 99%